The Effects of Family Contact on Community Reentry Plans Among Incarcerated Youths. Issue 5 (4th July 2018) - Ruch, Donna A.; Yoder, Jamie R.
ABSTRACT: Research shows protective factors that mitigate risks for juvenile delinquency can also support the community reentry of incarcerated youths and deter future offending. Family engagement, educational attainment, and secure employment are widely accepted as important protective factors to prevent problematic behavior. Studies suggest these same protective factors are crucial for incarcerated youths and should be an integral part of reentry planning to improve post-release outcomes. Nevertheless, limited research exists on the association between these factors and the value of family involvement in reentry planning for incarcerated youths. This study addresses this gap by examining how increased family contact affects the likelihood of instituting education and employment reentry plans among youths in custody. Data were obtained from the Survey of Youth in Residential Placement (SYRP) that provides information on juvenile offenders in confinement. The SYRP is the first nationally representative cross-sectional survey to gather information directly from youths 10–20 years old in custody (N=7, 073). Analyses were conducted using a sequence of regression models to test the relationship between the frequency of family contact and whether a youth had a plan for education or employment upon release. Results reflect that youths with increased family contact were one and a half times more likely to have both educational and employment reentry plans in place relative to youths with no family contact. Findings inform practice and policy to advocate for family involvement with youth in confinement, and further suggest that family plays a decisive role in preparing incarcerated youths for success upon release.